2021
DOI: 10.1096/fj.202002650rr
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of VGLL4 in the regulation of chronic normobaric hypoxia‐induced pulmonary hypertension in mice

Abstract: Pulmonary hypertension (PH), a rare but deadly cardiopulmonary disorder, is characterized by extensive remodeling of pulmonary arteries resulting from enhancement of pulmonary artery smooth muscle cell proliferation and suppressed apoptosis; however, the underlying pathophysiological mechanisms remain largely unknown.Recently, epigenetics has gained increasing prominence in the development of PH. We aimed to investigate the role of vestigial-like family member 4 (VGLL4) in chronic normobaric hypoxia (CNH)-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Notably, our previous study found that VGLL4 protein expression increases time-dependently with hypoxia in C57BL/6 mice and is upregulated in systemic (e.g., heart, liver, lung, kidney, and brain) expression distribution all in response to hypoxia. 21 The response of VGLL4 to hypoxia exists as a coordination among various tissues that work together to improve hypoxic metabolism. Brain tissues are extremely sensitive to hypoxia for several reasons, 39 including low glucose and oxygen reserves in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, our previous study found that VGLL4 protein expression increases time-dependently with hypoxia in C57BL/6 mice and is upregulated in systemic (e.g., heart, liver, lung, kidney, and brain) expression distribution all in response to hypoxia. 21 The response of VGLL4 to hypoxia exists as a coordination among various tissues that work together to improve hypoxic metabolism. Brain tissues are extremely sensitive to hypoxia for several reasons, 39 including low glucose and oxygen reserves in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research 21 and Wang et al 22 found that VGLL4 is a key factor in the regulation of hypoxia-sensitive pathways. We then explored the hypoxia sensitivity of VGLL4 by treating SH-SY5Y and SAS cells with hypoxia for 0, 2, 4, 8, and 12 h. The results showed that the protein expression of VGLL4 and LDHA in SH-SY5Y cells increased with hypoxia in a time-dependent manner (Figure 4A-C), indicating that VGLL4 and LDHA can be sensitively regulated by hypoxic concentrations.…”
Section: Ldha Regulated By Vgll4 Is Reduced In Ad Model Cellsmentioning
confidence: 91%
See 1 more Smart Citation
“…This downregulation of MEIS1 was dependent on METTL14 m6A writer, which was highly upregulated under hypoxic conditions [139]. Additionally, PASMC proliferation can also occur via the STAT3 pathway [140]. This occurs when chronic normobaric hypoxia upregulates the expression of VGLL4, activating the SIRT1-mediated histone acetylation to contribute to pulmonary artery remodelling and the development of PH.…”
Section: Epitranscriptomic Modifications In Other Pulmonary Diseasesmentioning
confidence: 97%
“…VGLL4 can also target the Hippo-YAP/TEAD1 signaling pathway by inducing the degradation of TEAD1 to attenuate oxidative stress, inflammation, and dysfunction in HUVECs induced by ox-LDL [ 157 ]. In addition, VGLL4 promotes pulmonary hypertension and pulmonary arterial remodeling through a signal transducer and the activation of transcription 3 (STAT3) signaling [ 158 ]; alternatively, the specific knockout of VGLL4 in ECs increases the YAP expression and heart valve malformation [ 159 ].…”
Section: Future Prospects For Clinical Applicationsmentioning
confidence: 99%